Evolving Anti-VEGF Therapy For Diabetic Retinopathy: Current Evidence, Durability Strategies, And Future Directions - Ade John Nursalim Nursalim (CV. AFDIFAL MAJU BERKAH, 2026)
Diabetic retinopathy (DR) remains one of the leading causes of vision impairment and blindness among working-age adults worldwide. The introduction of anti-vascular endothelial growth factor (anti-VEGF) therapy has significantly transformed the management of DR by effectively reducing retinal vascular permeability, inhibiting neovascularization, and improving visual outcomes. This article reviews the evolving role of anti-VEGF agents in the treatment of diabetic retinopathy, highlighting current clinical evidence regarding their efficacy, safety, and comparative performance. Particular attention is given to durability strategies designed to reduce treatment burden, including treat-and-extend regimens, high-dose formulations, sustained-release delivery systems, and emerging long-acting therapeutic approaches. The review also discusses the limitations of existing therapies, such as the need for frequent intravitreal injections, patient adherence challenges, and variability in treatment response. Furthermore, future directions are explored, including novel molecular targets, gene-based therapies, combination treatments, and advancements in personalized medicine supported by artificial intelligence and predictive biomarkers. The findings indicate that while anti-VEGF therapy remains the cornerstone of contemporary diabetic retinopathy management, ongoing innovations aimed at enhancing treatment durability and individualized care have the potential to improve long-term outcomes and reduce the global burden of diabetic eye disease.